Rapid synthesis and consolidation of nanostructured 2MgAl(2)O(4)-MgAl2Ti3O10 composite and its mechanical properties - Shon, In-Jin; Kang, Hyun-Su; Doh, Jung-Mann; Yoon, Jin-Kook (SPRINGER, 2014)
Rapid sintering of nanostructured 2MgAl(2)O(4)-MgAl2Ti3O10 composite in a pulsed current activated sintering process was investigated. The advantage of this process is that it enables very rapid densification to near theoretical density and prevents grain growth in nanostructured materials. Highly dense nanostructured 2MgAl(2)O(4)-MgAl2Ti3O10 composite was produced by simultaneous application of 80 MPa pressure and a pulsed current of 2,800 A for 2 min. The sintering behavior, grain size, and mechanical properties of the 2MgAl(2)O(4)-MgAl2Ti3O10 composite were investigated.
Keywords: FABRICATION; POWDERS; SPINEL